A study on the perception on the factors that contribute to the reckless riding behavior among motorcyclists: a case study at Jalan Hang Tuah, Melaka / Mohd Fazli Abdul Aziz and Mohd Hazwan Mohd Radzi - Abdul Aziz, Mohd Fazli; Mohd Radzi, Mohd Hazwan (Faculty of Administrative Science and Policy Studies, 2012)
A study has shown that distance, time and safety are the factors that contribute to the reckless riding behavior among motorcyclists. Distance can be defined as the amount of space between two places or things which determine the speed of motorcyclist in riding their motorcycle. Time constraints will increase the probability of a motorcyclist to ride motorcycles at high speed. Safety would define a person rides his or her motorcycle. A person tends to ride motorcycle faster when he or she ensure about their safety measurement when riding a motorcycle either long or short term or distance journey. Reckless driving behavior is a condition when a rider who aggressively driving or riding on the road as actual or intended behavior which resulting a physical or psychological harm to the victim experiences as such. With the increase number of new registered motorcycles on the road in Malaysia and outbreak of number of accident and casualties that among motorcyclists that mostly reported caused by the reckless riding behavior, it is important to know the relationship between distance, time and safety with the reckless riding behavior. Thus, this study to determine whether the distance, time and safety which are the independent variables have contributed to the reckless riding behavior among motorcyclists as the dependent variables at Jalan Hang Tuah, Melaka or vice versa. A purposive sampling of 200 respondents whom were motorcyclists from Jalan Hang Tuah, Melaka that work, live and study at Jalan Hang Tuah, Melaka has answered the questionnaires given. The independent variables were examined. The reckless riding behavior among motorcyclist at Jalan Hang Tuah, Melaka was significantly contributed by the factors namely distance, time and safety. The study indicates that there was a significant relationship between reckless riding behavior and the independent variables.